Abietane Diterpernoids from the Roots of Euphorbia ebracteolata - Yuan-Liang Ma; Xiao-Han Tang; Wen-Juan Yuan; Xiao Ding; Ying-Tong Di; Xiao-Jiang Hao (Natural Products and Bioprospecting, 2018)
Abstract A new ent-abietane diterpernoid, named ebracteolata D (1), along with 11 known analogues, was isolated from the roots of Euphorbia ebracteolata Hayata. The structure of 1 was elucidated on the basis of spectroscopic analysis and molecular modeling. Cytotoxicity of compounds 1–12 was evaluated as well as the effect on the NF-κB pathway. Among them, compound 12, jolkinolide B, displayed broad inhibitory effects against proliferation of tumor cell lines. Mechanistic studies indicated that the compound 12 can inhibit TNF-α induced NF-κB activation, thereby inducing tumor cell apoptosis. Graphical Abstract